Bioinsektisida Ekstrak Kulit Pisang Kepok (Musa paradisiaca) Terhadap Mortalitas Ulat Grayak (Spodoptera litura) pada Sawi Hijau (Brassica juncea L) - Intan Pramushinta (LPPM Universitas PGRI Adi Buana Surabaya, 2020)
The green mustard plant is a type of vegetable that is favored by the consumers. Green mustard plant production has decreased due to pest attacks. Pests that often attack and harm these food crops are armyworm. The way to control plant pests (OPT) was used bioinsecticides. This study was aimed to determine the effect of Kepok banana peel extract bioinsecticide (Musa paradisiaca) on the mortality of armyworm (Spodoptera litura), the growth (number of leaves) of greens mustard (Brassica juncea L.), and the production (wet weight) of greens mustard ( Brassica juncea L.). This study used a Completely Randomized Design (CRD) consisting of 4 treatments (0%, 5%, 10%, 15%) and 6 replications. Bioinsecticide was given to armyworm during the treatment and spraying 4 times a week on green mustard plants for 5 weeks. The research data were analyzed by using the ANOVA test, if the data has a significant effect, a further test would be carried out, namely the DUNCAN test. The results showed that administration of kepok banana peel extract bioinsecticide had a significant effect (P <0.05) on the number of armyworm mortality (F count 64.931> F table 3.10), green mustard plant growth (number of leaves) (F count 15.748> F table 3.10), and the production of green mustard (wet weight) (F count 9.298> F table 3.10). The DUNCAN test results showed that P3 treatment (15%) was significantly different compared to other treatments.